2014
DOI: 10.1051/0004-6361/201322498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the environment on galaxies in the Catalogue of Isolated Galaxies: physical satellites and large scale structure

Abstract: Context. We present a study of the 3D environment for a sample of 386 galaxies in the Catalogue of Isolated Galaxies (CIG, Karachentseva 1973) using the Ninth Data Release of the Sloan Digital Sky Survey (SDSS-DR9). Aims. We aim to identify and quantify the effects of the satellite distribution around a sample of galaxies in the CIG, as well as the effects of the large-scale structure (LSS). Methods. To recover the physically bound galaxies we first focused on the satellites that are within the escape speed of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…After compiling a first sample of primary galaxies using these conditions, we proceeded to clean the sample following a pipeline similar to the one developed in Argudo-Fernández et al (2014): (a) we selected all galaxies within at least 1 Mpc radius completely sampled by the SDSS-DR10 photometric footprint; (b) we performed a star-galaxy separation in order to reject stars misclassified as galaxies in the automated SDSS pipelines; and (c) we applied an automated cleaning process to discard multiple identifications of the same galaxy.…”
Section: Data and Definition Of The Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…After compiling a first sample of primary galaxies using these conditions, we proceeded to clean the sample following a pipeline similar to the one developed in Argudo-Fernández et al (2014): (a) we selected all galaxies within at least 1 Mpc radius completely sampled by the SDSS-DR10 photometric footprint; (b) we performed a star-galaxy separation in order to reject stars misclassified as galaxies in the automated SDSS pipelines; and (c) we applied an automated cleaning process to discard multiple identifications of the same galaxy.…”
Section: Data and Definition Of The Isolationmentioning
confidence: 99%
“…Star-galaxy separation and cleaning for multiple identifications as in Argudo-Fernández et al (2014) were also performed to avoid duplication in the neighbour sample.…”
Section: Data and Definition Of The Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…The systems are isolated with no neighbours in a volume of 1 Mpc projected distance within a line-of-sight velocity difference of ∆ ≤ 500 km s −1 . After defining isolation, they followed a similar method as in Argudo-Fernández et al (2014) to identify the physically bound isolated pairs. For the central galaxy in isolated pairs, Argudo-Fernández et al (2015b) found an over-density of neighbours in the two-dimensional (2D) distribution of ∆ and distance d. This over-density indicates that those neighbours are likely to be physically connected.…”
Section: Isolated Galaxies and Isolated Pairsmentioning
confidence: 99%
“…Galaxy clusters have been extensively used to study galaxy evolution because they allow us to discern between nature and nurture galaxy evolutionary processes [1,2]. For simplicity, hereafter, we refer to the intra-cluster medium (ICM) as the hot medium of both groups and clusters of galaxies.…”
Section: Introductionmentioning
confidence: 99%